Adaptive crossing numbers and their application to binary downsampling - Decenciere, Etienne (Image analysis and stereology, 2007)
A downsampling method for binary images is presented, which aims at preservingthe topology of the image. It uses a general reference sampling structure. The reference image is computed through the analysis of the connected components of the neighbourhood of each pixel. The resulting downsampling operator is autodual, which ensures that white and black structures are treated in the same way. Experiments show, by visual inspectionon the displayed images, that the image topology is indeed preservedsatisfactorily.
Keywords: Image Processing, Computer-Assisted; Slika, obdelava z računalnikom; Sample Size; Vzorec, razpoznavanje; Vzorec, velikost; Pattern Recognition; digitalna topologija; vzorci; dvodimenzionalna slika; metode